2010
DOI: 10.1016/j.juro.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Controlled Trial of Transureteral and Shock Wave Lithotripsy—Which is the Best Minimally Invasive Modality to Treat Distal Ureteral Calculi in Children?

Abstract: In the short term it seems that transureteral and shock wave lithotripsy are acceptable modalities for the treatment of distal ureteral calculi in children. However, transureteral lithotripsy has a higher efficacy rate when performed meticulously by experienced hands using appropriate instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…The available methods include medical expulsive therapy, SWL, ureterolithotripsy using semirigid or flexible tools and pneumatic or laser lithotriptor, PAU, laparoscopic ureterolithotomy, and open surgery [7]. Current literature data suggest variable success rates [7, 8]. The aim of treatment should be to provide freedom of stones as soon and as safely as possible and with the least invasive procedure possible.…”
Section: Discussionmentioning
confidence: 99%
“…The available methods include medical expulsive therapy, SWL, ureterolithotripsy using semirigid or flexible tools and pneumatic or laser lithotriptor, PAU, laparoscopic ureterolithotomy, and open surgery [7]. Current literature data suggest variable success rates [7, 8]. The aim of treatment should be to provide freedom of stones as soon and as safely as possible and with the least invasive procedure possible.…”
Section: Discussionmentioning
confidence: 99%
“…SFR was remarkably higher in the transurethral lithotripsy group than in the SWL group (respectively P < 0.004 and P < 0.001) and need to repeat the treatment in SWL was higher than transurethral lithotripsy (TUL) (P < 0.004). 33 In a case report, Hosseini et al in 2011 presented a patient with a solid stony mass which was in the perineum after Two-Stage Urethroplasty. They concluded that Ho: YAG laser is a minimally invasive modality which is suitable for management of urethral stones in such cases.…”
Section: Treatment Of Urolithiasis With Lasermentioning
confidence: 99%
“…However, effi cacy rates were higher in the ureteroscopy group. Two patients sustained ureteral perforation during ureteroscopy, other complications in both groups were minor [ 33 ]. In our opinion, the small size of urethra und ureter in young children favors SWL as primary treatment in children with ureteral stones.…”
Section: Ureteric Stones In Childrenmentioning
confidence: 66%